A Study on Digital Learning Scope and Challenges in Indian Society - Saidaiah, Kamissetty; K. Ravishankar, Dr. (International Journal of Engineering and Technology, 2018)
Education plays necessary role in overall development of people thereby conducive vastly to the development of a nation. Education globally is one amongst the necessary sectors to witness revolutionary changes in recent times. This happens primarily attributable to digital revolution taken place all across the world. the standard Indian room was once characterized by students sitting through hour-long session, teacher accustomed discuss the items with none visual presentation. Now, because of digital technology, it's creating life easier for each students and educators. Digital education is fun learning for all cadres and significantly effective for kid learning because the innovative audio-video feature boosts the psychological feature parts in an exceedingly childâ€™s brain. faculties square measure progressively adopting digital teaching solutions in their tutorial, and making an attempt to form the room setting a lot of comprehensive and democratic. The INFO-TAINMENT combination concerned in digital education makes it a lot of sensible, applicable and relatable to our life and surroundings in a remarkable manner. In India, from previous few years there has been a substantial rise in Digital and Live Virtual lecture rooms at completely different levels of learning. With evolution of technologies like cloud, virtual knowledge centerâ€™s and virtualization there's immense potential for technology to be integrated with the Education trade. the aim of this analysis is to present summary of digital education, elements of digital education, edges of digital education in Asian nation, the long run scope And doable challenges of an Indian society for moving towards digital education.Â Â